Enkele motiewe vir "n eietydse verstaan van die belydenisskrifte - Koekemoer, J. H. (Hervormde teologiese studies, 1997)
Reasons for a comtemporary re-interpretation of creeds. The present century has seen an increasing opposition to creeds and doctrinal statements of faith. The question for the church and theology is how to read the creeds in such a way that it will not deprive us from our own responsibility to Scripture. In order to do just that a reinterpretation of the creeds is necessary. In this reinterpretation there should be a recognition of historical and cultural relativity. We do not experience our world in the same way as premodern people did. Any attempt to leave ecclesiastical doctrines in an unchangeable form would result in the increasing loss of the meanings of those doctrines.